A Binary Decision Diagram based on-line testing of digital VLSI circuits for feedback bridging faults. Issue 7 (July 2015) - Biswal, Pradeep Kumar; Biswas, Santosh
Abstract Classical manufacturing test verifies that a circuit is fault free during fabrication, however, cannot detect any fault that occurs after deployment or during operation. As complexity of integration rises, frequency of such failures is increasing for which on-line testing (OLT) is becoming an essential part in design for testability. In majority of the works on OLT, single stuck at fault model is considered. However in modern integration technology, single stuck at fault model can capture only a small fraction of real defects and as a remedy, advanced fault models such as bridging faults, transition faults, delay faults, etc. are now being considered. In this paper we concentrate on bridging faults for OLT. The reported works on OLT using bridging fault model have considered non-feedback faults only. The basic idea is, as feedback bridging faults may cause oscillations, detecting them on-line using logic testing is difficult. However, not all feedback bridging faults create oscillations and even if some does, there are test patterns for which the fault effect is manifested logically. In this paper it is shown that the number of such cases is not insignificant and discarding them impacts OLT in terms of fault coverage and detection latency. The present work aims at developing an OLT scheme for bridging faults including the feedback bridging faults also, that can be detected using logic test patterns. The proposed scheme is based on Binary Decision Diagrams, which enables it to handle fairly large circuits. Results on ISCAS 89 benchmarks illustrate that consideration of feedback bridging faults along with non-feedback ones improves fault coverage, however, increase in area overhead is marginal, compared to schemes only involving non-feedback faults.